2002
DOI: 10.3354/cr019247
|View full text |Cite
|
Sign up to set email alerts
|

Long-term variability in reconstructed and observed snow cover over the last 100 winter seasons in Cracow and Zakopane (southern Poland)

Abstract: An attempt to reconstruct the seasonal snow cover data in Cracow (for 26 winter seasons) and Zakopane (for 19 winter seasons) at the turn of the 20th century based on climatic data was made by using multiple regression. The results of the reconstruction were more successful for the station located at lower altitude (Cracow, 206 m above sea level) and allowed an analysis of nival conditions to be extended over 104 winter seasons. The reconstructed data obtained for Zakopane (857 m above sea level) appear to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 5 publications
1
28
0
Order By: Relevance
“…Pińskwar [40] and Niedźwiedź et al [41] discovered upward trends in the analyzed metrics of daily rainfall that were, however, not significant again. Also Falarz [42], who investigated the time of snow cover presence, observed a downward but insignificant trend for this phenomenon. Similarly, Kundzewicz et al [22] reported that the presence of trends for climatic The highest values of Q max in the investigated river catchments were recorded in 1997, 1998 and 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Pińskwar [40] and Niedźwiedź et al [41] discovered upward trends in the analyzed metrics of daily rainfall that were, however, not significant again. Also Falarz [42], who investigated the time of snow cover presence, observed a downward but insignificant trend for this phenomenon. Similarly, Kundzewicz et al [22] reported that the presence of trends for climatic The highest values of Q max in the investigated river catchments were recorded in 1997, 1998 and 2010.…”
Section: Resultsmentioning
confidence: 99%
“…During the last 62 years, it varied from 107 days in 1989 to 177 days in 1952. The number of days with snow cover in the Tatra Mountains increases with altitude at a rate of 9 days 100 m −1 and varies from less than 120 days at the mountain base to about 220-290 days on the highest peaks (Hess 1965 A statistically significant decreasing trend of snow cover duration (−8 days 10 years −1 ) and maximum snow cover depth (−9 cm 10 years −1 ) has been detected in Zakopane for the period 1961-1990(Falarz 2002. No such trend can, however, be found at the scale of the twentieth century (period 1915-1999).…”
Section: The Basics Of the Tatra Mountains Climatementioning
confidence: 99%
“…Brown, 2000;Mote, 2003;Huntington et al, 2004;McCabe and Wolock, 2010), several studies have documented decreases in snow precipitation, snow depths, snow cover durations or snow water equivalent in many countries of the Alpine region (e.g. Falarz, 2002Falarz, , 2004Laternser and Schneebeli, 2003;ONERC, 2008;Valt and Cianfarra, 2010;Serquet et al, 2011;Marty and Meister, 2012). Increased variability has also been observed, especially for winter temperatures, inducing an increasing number of warm winter spells (Beniston, 2005a).…”
Section: Introductionmentioning
confidence: 99%